Anamorelin HCl (ONO‐7643), a novel ghrelin receptor agonist, for the treatment of cancer anorexia‐cachexia syndrome: preclinical profile. Issue 4 (30th September 2014) - Pietra, Claudio; Takeda, Yasuhiro; Tazawa-Ogata, Naoko; Minami, Masashi; Yuanfeng, Xia; Duus, Elizabeth Manning; Northrup, Robert
Abstract : Background: Anamorelin HCl (ANAM) is a novel, orally active, ghrelin receptor agonist in clinical development for the treatment of cancer cachexia. We report in vitro and in vivo studies evaluating the preclinical pharmacologic profile of ANAM. Methods: Fluorescent imaging plate reader and binding assays in HEK293 and baby hamster kidney cells determined the agonist and antagonist activity of ANAM, and its affinity for the ghrelin receptor. Rat pituitary cells were incubated with ANAM to evaluate its effect on growth hormone (GH) release. In vivo, rats were treated with ANAM 3, 10, or 30 mg/kg, or control orally, once daily for 6 days to evaluate the effect on food intake (FI) and body weight (BW), and once to assess GH response. In pigs, single (3.5 mg/kg) or continuous (1 mg/kg/day) ANAM doses were administered to assess GH and insulin‐like growth factor (IGF‐1) response. Results: ANAM showed significant agonist and binding activity on the ghrelin receptor, and stimulated GH release in vitro. In rats, ANAM significantly and dose‐dependently increased FI and BW at all dose levels compared with control, and significantly increased GH levels at 10 or 30 mg/kg doses. Increases in GH and IGF‐1 levels were observed following ANAM administration in pigs. Conclusion: ANAM is a potent and highly specific ghrelin receptor agonist with significant appetite‐enhancing activity, leading to increases in FI and BW, and a stimulatory effect on GH secretion. These results support the continued investigation of ANAM as a potential treatment of cancer anorexia‐cachexia syndrome.